The effects of participation in movement programs on the movement competence, self-esteem and resiliency of adolescent girls - Jonathan, Bronwyn Bock (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Sport Science))—University of Stellenbosch, 2008.